The influence of the mining unions over the employees’ socio-economical conditions in the Jiu valley - Ciocodeică, Vasile (НТУ "ХПІ", 2010)
Clause has grasped some facts, which are present at valley Jiu and also, more deeply to understand them, is analyzed existing reality through the last actions. The general situation of the Romanian world of the un-ion Is represented. After that used historical prospect on a current situation of the extracting unions in valley Jiu and their becoming

Стаття захопила кілька фактів, які присутні в долині Жіу і також, щоб глибше їх розуміти, аналізується існуюча дійсність через минулі дії. Представляється загальна ситуація румунського світу союзу. Після цього використовували історичну перспективу по поточній ситуації видобувних спілок в долині Жіу і їх становленні
Вплив союзiв гірської промисловості по соціо-економiчним умовам службовців у долинi Жiу